The synchrony of production and escape: half the bright Lyα emitters at z ≈ 2 have Lyman continuum escape fractions ≈50. Issue 3 (11th December 2021) - Naidu, Rohan P; Matthee, Jorryt; Oesch, Pascal A; Conroy, Charlie; Sobral, David; Pezzulli, Gabriele; Hayes, Matthew; Erb, Dawn; Amorín, Ricardo; Gronke, Max; Schaerer, Daniel; Tacchella, Sandro; et al.
ABSTRACT: The ionizing photon escape fraction [Lyman continuum (LyC) f esc ] of star-forming galaxies is the single greatest unknown in the reionization budget. Stochastic sightline effects prohibit the direct separation of LyC leakers from non-leakers at significant redshifts. Here we circumvent this uncertainty by inferring f esc using resolved ( R  > 4000) Lyman α (Lyα) profiles from the X-SHOOTER Lyα survey at z = 2 (XLS- z 2). With empirically motivated criteria, we use Lyα profiles to select leakers ($f_{\mathrm{ esc}} > 20{{\ \rm per\ cent}}$ ) and non-leakers ($f_{\mathrm{ esc}} < 5{{\ \rm per\ cent}}$ ) from a representative sample of >0.2 L * Lyman α emitters (LAEs). We use median stacked spectra of these subsets over λrest  ≈ 1000–8000 Å to investigate the conditions for LyC f esc . Our stacks show similar mass, metallicity, M UV, and βUV . We find the following differences between leakers versus non-leakers: (i) strong nebular C iv and He ii emission versus non-detections; (ii) [O iii ]/[O ii ] ≈ 8.5 versus ≈3; (iii) Hα/Hβ indicating no dust versus E ( B − V ) ≈ 0.3; (iv) Mg ii emission close to the systemic velocity versus redshifted, optically thick Mg ii ; and (v) Lyα f esc of ${\approx} 50{{\ \rm per\ cent}}$ versus ${\approx} 10{{\ \rm per\ cent}}$ . The extreme equivalent widths (EWs) in leakers ([O iii ]+$\mathrm{ H}\beta \approx 1100$  Å rest frame) constrain the characteristic time-scale of LyC escape to ≈3–10 Myr bursts when short-lived stars with the hardest ionizing spectra shine. The defining traits of leakers – extremely ionizing stellar populations, low column densities, a dust-free, high-ionization state interstellar medium (ISM) – occur simultaneously in the $f_{\rm esc} > 20{{\ \rm per\ cent}}$ stack, suggesting they are causally connected, and motivating why indicators like [O iii ]/[O ii ] may suffice to constrain f esc at z > 6 with the James Webb Space Telescope ( JWST ). The leakers comprise half of our sample, have a median LyC$f_{\rm esc} \approx 50{{\ \rm per\ cent}}$ (conservative range: $20\!-\!55{{\ \rm per\ cent}}$ ), and an ionizing production efficiency $\log ({\xi _{\rm {ion}}/\rm {Hz\ erg^{-1}}})\approx 25.9$ (conservative range: 25.7–25.9). These results show LAEs – the type of galaxies rare at z  ≈ 2, but that become the norm at higher redshift – are highly efficient ionizers, with extreme ξion and prolific f esc occurring in sync.